Enhancing Data Security Using Audio-Video Steganography - Mudusu, Rambabu; Nagesh, A; Sadanandam, M (International Journal of Engineering and Technology, 2018)
Steganography may be a strategy for concealing any mystery information like content, picture, sound behind distinctive cowl document .In this paper we have a tendency to planned the mix of image steganography associated sound steganography with confront acknowledgment innovation as an instrument for verification. The purpose is to shroud the mystery information behind sound and therefore the beneficiary's face image of video, because it may be a use of various still casings of images and sound. During this technique we've chosen any casing of video to shroud beneficiary's face image and sound to hide the mystery data. Affordable calculation, maybe, increased LSB and RSA rule is been utilised to shroud mystery content and movie. PCA rule is employed for confront acknowledgment. The parameter for security and verification ar gotten at collector and transmitter facet that ar exactly indistinguishable, consequently the knowledge security is dilated.Â